The Managementof Community-Based Irrigation System (A Case Study of Water Users’ (Farmers) Association in Suak, Manis Raya Village, Sepauk District, Sintang Regency) - Deni Ratnasari; Zaenal Kusuma; Imam Hanafi (Graduate Program, 2018)
Water user farmer association (P3A) is an organization closely related to regulation of irrigation water in a tertiary or village plot service area formed by farmers or farmer groups in a democratic village. The role of P3A is to manage irrigation water and water distributors fairly and evenly in tertiary / stronger printing. The research aims to analyze the management of community-based irrigation system by P3A in Suak Village of Manis Raya Village of Sepauk Subdistrict of Sintang Regency and to Analyze the inhibiting factors in the management of irrigation system. The research was done by descriptive method and qualitative analysis. Data obtained from interviews, literature, and field observations, then analyzed and interpreted by giving conclusions. The results of the research indicate that (1) the institutional aspect, irrigation network in Suak sub village has no institution of water user farmer association (P3A), (2) HR aspect, farmer of Dusun Suak has adequate human resources seen from age, education, social economy and work ability. (3) Aspects of facilities and infrastructure, facilities and infrastructure of farmers in the village of Suak are still limited, farmers have not been able to utilize existing facilities and infrastructure. (4) Aspects of irrigation systems, farmers are still freely flowing water without regulation, irrigation maintenance is done when there is government funding, the main dam leaked for the last two years has not been fixed. Farmers' awareness of irrigation networks is not yet available. The inhibiting factor of irrigation system management is that there is no P3A institution yet, the participation of farmers is limited, the fund is limited. From the results of the research, irrigation management in the village of sweet is still not implemented maximally either from government or from society, seen from condition of irrigation network which often happened accumulation of garbage and weeds. In addition, community participation is still very poor. Irrigation management in the hamlet of Suak has not been well managed by the farmers either in the maintenance of irrigation networks, as well as the distribution of farmers' peat water because there is no P3A organization that regulates irrigation management and water distribution. Irrigation management can be sustainable should the cooperation between stakeholders.Keywords: Farmers’ Participation, Irrigation System Management, P3A